Use of a jugular vein model for the instruction of equine intravenous catheter placement by third‐and fourth‐year veterinary students. (21st February 2020) - Hobbs, K. J.; Johnson, P. J.; Scharf, M. E.; Cross, D. T.; Wallace, L. L.
Summary: Successful placement of an i.v. catheter in horses is a core competency required by the AVMA COE accreditation policy (section 7.11, #2, #3, #5). Therefore, we determined whether the use of a novel intravenous (i.v.) catheter placement training tool would improve confidence, time to successful placement and accuracy with which third‐ and fourth‐year veterinary students acquire competence regarding this skill in adult horses. Students lacking earlier experience with i.v. catheter placement in horses were randomly assigned to either Group 1 (n = 15) or 2 (n = 10). Students with prior experience with the technique were assigned to Group 3 (n = 14). Group 1 students were instructed on i.v. catheter placement using the model and then assessed using a live horse. Group 2 students were instructed on i.v. catheter placement using a live horse and then assessed using a live horse. Group 3 students were assessed using a live horse. Assessments included number of placement attempts, number of redirects and time needed to achieve correct intraluminal placement. Student perceptions regarding the use of this model for the purpose of learning i.v. catheter placement in horses were evaluated using a questionnaire. Results of this study demonstrated that students receiving initial instruction with the model achieved better scores in terms of both time to accomplish the task and accuracy for catheter placement in a live horse when compared with students that received their first instruction on a live horse. The use of this i.v. catheter placement training tool therefore served to lessen the cost of training and to minimise animal discomfort during this component of veterinary student training.